Bernardo Navarro y Ovidio González. Metro, metrópoli, México. México : UNAM : UAM, 1989. 167 p. - Muñoz Contreras, María Elena (Estudios Demográficos y Urbanos, 1990)
BERNARDO NAVARRO Y OVIDIO GONZÁLEZ, Metro, Metrópoli, México, UNAM/UAM, México, 1989.